PENERAPAN PENDEKATAN KONTEKSTUAL MELALUI TEAM ASSISTED INDIVIDUALIZATION UNTUK MENINGKATKAN PEMAHAMAN KONSEP - Zendrato, Idaman (JURNAL PENA EDUKASI, 2018)
Abstract: The Team Assisted Individualization cooperative learning model is learning that combines the advantages of cooperative learning and individual learning. This type is designed to overcome student learning difficulties individually. Limitation of the problem in this study is limited to the low understanding of students' concepts on mathematics subjects especially in integer material and learning which is dominated by teachers so students are less involved in learning. The formulation of the problem in this study is whether the application of the scientific approach through cooperative learning models Team Assisted Individualization types can improve understanding of concepts in integer material. So the purpose of this study was to determine whether the application of the scientific approach through cooperative learning models Team Assisted Individualization type can improve concept understanding of integer material and to describe the process of applying the scientific approach through the Team Assisted Individualization (TAI) type cooperative learning model. From the learning process that researchers did in the first (first) cycle the average learning outcomes reached 72. In the second cycle (two) the average learning outcomes reached 85. Keywords: Contextual Approach, Team Assisted Individualization (TAI) Abstrak: Model pembelajaran kooperatif tipe Team Assisted Individualization adalah pembelajaran yang mengkombinasikan keunggulan pembelajaran kooperatif dan pembelajaran individual. Tipe ini dirancang untuk mengatasi kesulitan belajar siswa secara individual. Batasan masalah dalam penelitian ini terbatas pada rendahnya pemahaman konsep siswa pada mata pelajaran matematika khususnya pada materi bilangan bulat dan pembelajaran yang didominasi oleh guru sehingga siswa kurang dilibatkan dalam pembelajaran. Rumusan masalah dalam penelitian ini adalah apakah dengan penerapan pendekatan saintifik melalui model pembelajaran kooperatif Tipe Team Assisted Individualization dapat meningkatkan pemahaman konsep pada materi bilangan bulat. Maka tujuan penelitian ini adalah untuk mengetahui apakah dengan penerapan pendekatan saintifik melalui model pembelajaran kooperatif Tipe Team Assisted Individualization dapat meningkatkan pemahaman konsep pada materi bilangan bulat dan untuk mendeskripsikan proses penerapan pendekatan saintifik melalui model pembelajaran kooperatif Tipe Team Assisted Individualization (TAI). Dari proses pembelajaran yang peneliti lakukan pada siklus I (pertama) rata-rata hasil belajar mencapai 72. Pada siklus II (dua) rata-rata hasil belajar mencapai 85. Kata kunci: Pendekatan Kontekstual, Team Assisted Individualization (TAI)